Oblivio gate - Nevin, Sean, 1969- (Crab Orchard award series in poetry., 2008)
Suffused with lyrical grace and the language of loss, Sean Nevin's Oblivio Gate explores the mental and emotional struggles of Solomon, a veteran battling the onslaught of Alzheimer's disease. Set against Solomon's memories of the Korean War, Nevin's poems draw us into an intimate view of a man's confusion as everything he knows slowly unravels around him, leaving him abandoned in the suddenly unfamiliar landscape of his own mind. Readers experience first- hand Solomon's dismay as he watches himself inexorably slip away from reality, fighting to hold on to the shred.